Effectiveness of physical barriers and enhanced fertilization in controlling predation on tilapia and catfish aquaculture systems by four piscivorous water bird families - Otieno, Nickson Erick; Shidavi, Erick (Frontiers in Sustainable Food Systems, 2022)
Waterbirds cause substantial fish-stock losses in open aquaculture systems, particularly in developing countries where fish-ponds are smaller and predator control methods largely manual or under-resourced. This study: (1) used three fish-pond treatment meassures to assess their efficiencies in deterring predation pressure by four piscivorous waterbird families in small tilapia and catfish farms in western Kenya; and (2) distinguished bird group(s) most effectively deterred by these measures. The treatment measures were: coarse-grid wire mesh barriers; finer-grid wire barriers; and enhanced pond fertilization. Twelve fish-ponds were randomly sampled to assess birds' pond-neigborhood assemblages and their predation deterrence responses to pond treatment effects. Bird species richness was not affected by pond cover status, enhanced pond fertilization or type of pond cover barrier. However, pond-cover status, singularly and interactively with enhanced fertilization, reduced bird encounter rates while cover barrier type did not. Conversely, cover status, cover barrier type and fertilization each separately but not interactively contributed to improved deterrence to bird predation rates overall. However, while predation by families of larger birds was effectively reduced by enhancing pond fertilization or cover barriers, predation by families of smaller birds was prevented only by fine-grid chicken-mesh barriers. These results demonstrate that using enhanced fertilization and physical barriers can significantly contribute to reduction in predation pressure on open-culture pond-fish by most piscivorous birds, but may not always be effective if used separately. Effectiveness of combination of measures chosen will depend on types of target bird species and their feeding habits. The results constitute additional knowledge on field techniques useful in diversifying solution options for minimizing impacts of vertebrate predation on pond-fish stocks toward promoting sustainable aquaculture production and improving rural human nutrition.